Cloning and functional analysis of spliced isoforms of human nuclear factor I-X: interference with transcriptional activation by NFI/CTF in a cell-type specific manner. - Apt, D (1994)
Previous studies of the epithelial specificity of the human papillomavirus type 16 (HPV-16) enhancer pointed out an important role of nuclear factor I (NFI). In epithelial cells, NFI proteins are derived from the NFI-C gene and referred to as NFI/CTF. In contrast, fibroblasts, where the enhancer is inactive, express high levels of NFI from the NFI-X gene. To compare NFI-C and NFI-X derived transcription factors, we cloned and functionally investigated two differentially spliced forms of NFI-X from human fibroblasts. NFI-X1 has 95% homology with a transcript previously identified in hamster liver cells. NFI-X2, a spliced variant, misses 41 amino acids of the proline-rich activation domain. NFI-X expression, examined by Northern blots, shows strong cell-type specific variation in comparison with NFI/CTF. While the transcriptional activation domain of NFI-X2, functionally tested as GAL4-fusion protein in epithelial and fibroblast cells, activates transcription from promoter as well as enhancer position similar to NFI/CTF-1, the activation domain of NFI-X1 fails to activate transcription from enhancer position. In Drosophila cells, void of endogenous NFI proteins, full length NFI/CTF-1 and NFI-X2 activate a reporter construct containing only NFI sites as well as the NFI dependent HPV-16 enhancer. In contrast, NFI-X1 fails to activate the HPV-16 enhancer. Furthermore, overexpression of NFI-X1 in epithelial cells down-regulates the HPV-16 enhancer. Our findings suggest that the family of NFI transcription factors should not be viewed as constitutive activators, but rather, that NFI-C and NFI-X have divergent functions after binding in promoter or enhancer position. This property, combined with the differential expression of NFI-X, can achieve cell-type specificity of NFI dependent promoters and enhancers.